Early intervention everyday : embedding activities in daily routines for young children and their families - Crawford, Merle J.; Weber, Barbara (Baltimore, Maryland : Paul H. Brookes Publishing, 2014)
Effective early intervention doesn$1 (Bt stop when the provider leaves the family$1 (Bs home. That$1 (Bs why every interventionist needs this practical sourcebook, packed with research-based strategies for helping parents and caregivers take a consistent, active role in supporting young children$1 (Bs development. Targeting 80 skills in 6 key developmental domains for children birth to three, this reader-friendly guide gives professionals dozens of ready-to-use ideas for helping families and caregivers embed learning opportunities in their everyday routines. Early interventionists will turn to this book again and again for strategies that enhance child development, strengthen attachment, and help children with developmental delays participate fully in family life.s
Part 1. Early intervention basics and recommended practices -- 1. Overview of early intervention -- 2. Recommended practices: caregivers -- 3. Recommended practices: facilitating skill acquisition -- Part 2. Developmental progression of skills -- 4. Behavior regulation and social skills -- 5. Cognitive and receptive language -- 6. Expressive language -- 7. Gross-motor skills -- 8. Fine motor skills -- 9. Self-care/adaptive skills -- Part 3. Daily routines across domains.
Includes bibliographical references and index.
Keywords: CHILDREN WITH DISABILITES -- EDUCATION